2006
DOI: 10.1177/0146621606288554
|View full text |Cite
|
Sign up to set email alerts
|

Item Diffficulty Modeling of Paragraph Comprehension Items

Abstract: Recent assessment research joining cognitive psychology and psychometric theory has introduced a new technology, item generation. In algorithmic item generation, items are systematically created based on specific combinations of features that underlie the processing required to correctly solve a problem. Reading comprehension items have been more difficult to model than other item types due to the complexities of quantifying text. However, recent developments in artificial intelligence for text analysis permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 40 publications
6
75
0
2
Order By: Relevance
“…In the AnalyticalReasoning stimuli, "if" clauses are regularly used and could be expected to increase the difficulty of a text (both with respect to logical reasoning and sentence complexity). Based on work by Drum, Calfee, and Cook (1981); Embretson and Wetzel (1987); and Gorin and Embretson (2006).…”
Section: Cardinality Of Entitiesmentioning
confidence: 99%
“…In the AnalyticalReasoning stimuli, "if" clauses are regularly used and could be expected to increase the difficulty of a text (both with respect to logical reasoning and sentence complexity). Based on work by Drum, Calfee, and Cook (1981); Embretson and Wetzel (1987); and Gorin and Embretson (2006).…”
Section: Cardinality Of Entitiesmentioning
confidence: 99%
“…Following modern theoretical models, reading is considered an active and creative process of so called 'text image generation ' (van Dijk, Kintsch 1983, Kintsch 1988, Leontyev 1997) that includes a) (re-)encoding (also called 'decoding'), and b) elaboration of connection (coherence) between words and relating of word units in a logically coherent structure, i.e. text base (Gorin, Embretson 2006). According to Walter Kintsch and Teun A.van Dijk (1978), text processing can be interpreted as an iteration of the construction and integration processes.…”
Section: Introductionmentioning
confidence: 99%
“…This line of research has been built on the investigation (mainly through semi-structured interviews and verbal selfreports) into the strategies used by subjects to solve reading comprehension items (Farr, Pritchard & Smitten, 1990;DeMauro, Merritty & Adams, 1994;Powers & Wilson, 1995;Rupp, Ferne & Choi, 2006). In addition, the attempt to predict item difficulty level has generated a large number of studies where the basic interest has been to identify cognitive and linguistic predictors (Drum, Calfee & Cook, 1981;Stahl & Jacobson, 1986;Davey, 1988;Kirsch & Mosenthal, 1990;Freedle & Kostin, 1991;Freedle & Kostin, 1992;Daneman & Hannon, 2001;Sheehan & Ginther, 2001;Gorin & Embretson, 2006;Ozuru, Rowe, O'Reilly & McNamara, 2008;Leroy, Helmreich & Cowie, 2010). These last studies have primarily used a quantitative approach, making use of traditional statistical techniques such as multiple regression and ANOVA; however, various studies can also be found where the LLTM is used to estimate the predictive power of certain characteristics of logical reasoning and reading comprehension items (Embretson & Wetzel, 1987;Sheehan & Mislevy, 1990;Gorin, 2005;Sonnleitner, 2008;Attoresi, Picón, Abal, Aguerri & Galibert, 2009;Gilbert, Picón, Lozzia, Aguerri & Attorresi, 2010;Poinstingl, 2009).…”
mentioning
confidence: 99%